Acupuncture-related techniques for prevention of type 2 diabetes mellitus in people with pre-diabetes: Protocol for a systematic review and meta-analysis. Issue 45 (11th November 2022) - Guo, Haoze; Wu, Xingquan; Lei, Siyuan; Wang, Ying; Sun, Weichen; Yang, Qingwei; Song, Bailin
Abstract : Background: In modern society, the incidence of diabetes is increasing year by year. Most individuals pass through a phase of prediabetes before developing full blown diabetes. Acupuncture-related has been widely used in the treatment of diabetes, but there is no systematic review of acupuncture-related on the control of blood glucose in prediabetes. Therefore, this study aims to conduct a meta-analysis of the clinical efficacy of acupuncutre-related therapy in preventing the development of diabetes in patients with prediabetes. Methods: We will search Web of Science, The Cochrane Library, PubMed, Embase, Chinese Biomedical Literature Database (CBM), China National Knowledge Infrastructure (CNKI), Wan-Fang Database, Chinese Scientific Journal Database (VIP Database) from their respective inception dates to September 1, 2022 to identify potentially eligible studies. We will use the Review Manager 5.4 software provided by the Cochrane Collaborative Network for statistical analysis. We then assessed the quality and risk of the included studies and observed the outcome measures. Results: This meta-analysis further elucidates the protective effects of acupuncture-related techniques on patients with prediabetes. Conclusion: The purpose of this meta-analysis was to investigate the effect of acupuncture- related techniques on blood glucose in patients with prediabetes, and to provide more methods for clinical prevention of conversion from prediabetes to diabetes.